2016
DOI: 10.1002/hpm.2338
|View full text |Cite
|
Sign up to set email alerts
|

Health services utilization of people having and not having a regular doctor in Canada

Abstract: Canada having a universal health insurance plan that provides hospital and physician benefits offers a natural experiment of whether continuity of care actually provides lower or higher utilization of services. The question we are evaluating is whether Canadians, who have a regular physician, use more health resources than those who do not have one? Using two statistical methods, including propensity score matching and zero-inflated negative binomial regression, we analyzed data from the 2010 and 2007/2008 Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Multiple strategies may have a role in increasing the continuity of care and quality of care and improving patient outcomes, many of which may reduce hospitalization and ED visits of African American older adults with multiple CMCs. While the index condition (DM) is important, improving self-management of other comorbid conditions such as heart disease, hypertension, and asthma should not be discounted [59]. Such interventions may reduce health disparities among undeserved minority older adults with multiple comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple strategies may have a role in increasing the continuity of care and quality of care and improving patient outcomes, many of which may reduce hospitalization and ED visits of African American older adults with multiple CMCs. While the index condition (DM) is important, improving self-management of other comorbid conditions such as heart disease, hypertension, and asthma should not be discounted [59]. Such interventions may reduce health disparities among undeserved minority older adults with multiple comorbid conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that living in areas covered by primary healthcare with FHS presented favorable results for use of health services 30,31 . Other countries with effective primary healthcare also achieved positive results for use of health services and for achieving UHC 7,32,33 . Primary healthcare is essential for bridging the gap to UHC 34 .…”
Section: Place Of Last Dental Visitmentioning
confidence: 97%
“…Therefore, it is reasonable to assume that lack of continuity of care, a higher rate of frequent ED visits, combined with a longer waiting time at ED are significant factors contributing to health disparities among AA older adults. Current research shows that continuity of care improves quality of care, improves patient outcomes, reduces hospitalizations and decreases ED visits, particularly among older adults with CMCs that need self-management (e.g., heart disease, diabetes, hypertension, and asthma) [58]. Improving and maintaining continuity of care among older adults have the potential to reduce health disparities.…”
Section: Discussionmentioning
confidence: 99%